Effects of Information Providers, Channels and Types on the Adoption of Climate – Resilient Practices in Lesotho - Oladele, Oladimeji; Nthama, Nthapeliseng (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2024)
This study examined the effects of information providers, channels and types on the adoption of climate-resilient practices in Lesotho, deviating from the usual separate analysis of the relationships between information provider, channels and types. Previous studies have generated only partial insights into the influence of different information variables on adoption behaviour, neglecting a holistic representation of the interactive effects of all dimensions of information and adoption. Using a sample of 1,659 farmers from the Bureau of Statistics (BOS) database on the 2019/2020 agricultural production survey, the data was analysed using frequency counts, percentages and Probit regression. The results show that the majority of the farmers are male (53%), less than 30 years of age (59%), possess an education level between High School form 1 to 5 (59%), have between 5 and 10 persons per household (50%) and rely on subsistence farming as their main source of income (36%). The extension services provided, as indicated by at least 90% of the farmers, include information on farm management, crop selection, input use, credit, farm machinery, livestock, crop protection, conservation, marketing, irrigation and nutrition. In contrast, the information received is more focused on marketing, livestock production, agronomic practices, irrigation and fisheries production. The major extension service providers and sources of information are public service providers and radio. Agricultural extension information providers, channels and types influence the adoption of climate-resilient practices. The study recommends that extension information providers, channels and types be matched to specific contexts for improved effectiveness.